Trust is felt to be a Good Trigger in Marketing and Green Products in Generating Purchase Interest - I Nyoman Rasmen Adi; Made Mulyadi; I Nengah Wirsa; I Nengah Dasi Astawa; Made Setini (Universitas Mercu Buana, 2022)
Objective: This research was conducted with the aim of knowing the mediating role of trust in green products regarding the relationship between green product marketing awareness and product innovation on the purchase intention of environmentally friendly products.Methodology: This research is a quantitative research with the object of research are informants who already know as recycled fashion products, environmentally friendly drinking places, tissues, food containers and obtained 300 population data from distributing this questionnaire. The research instrument was distributed using a Google form. Using random sampling technique obtained 100 participants who already represent the representativeness of the data, analyzed by structural equation analysis (SEM) using the Smart PLS applicationResults: The findings of the study indicate that a direct relationship between green marketing awareness and product innovation has a positive influence on product purchase intentions. The direct relationship of trust felt by consumers has a positive influence on product purchase intentions. Mediating role Trust in products is able to mediate in awareness of green product marketing and product innovation on product purchase intentions. This means that the trust of customers must always be maintained in terms of the marketing we do and the products provided. Conclusion: Customers' trust in products that care about the environment that does not damage the environment is realized by a green marketing system so that this becomes a driving force for customers' buying intentions.